2012
DOI: 10.1155/2012/171706
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Herbal Patch for Short-Term Management of Knee Osteoarthritis: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Objective. To assess the short-term efficacy and safety of two kinds of Traditional Chinese herbal patches, Fufang Nanxing Zhitong Gao (FNZG) and Shangshi Jietong Gao (SJG), for painful knee osteoarthritis (OA). Methods. Patients were randomly enrolled in a double-blind, placebo-controlled study to receive FNZG (n = 60), SJG (n = 60), or placebo patch (n = 30) for 7 days. Outcome measures included visual analogue scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and Tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 9 publications
0
66
0
Order By: Relevance
“…A total of seven new studies were identified for inclusion in this updated review (Grube 2007; Kosuwon 2010; Randall 2000; Randall 2008; Soltanian 2010; Wang 2012; Widrig 2007). The one study of topical capsaicin that was included in the original review (Deal 1991) was excluded from this review when additional information that was provided by the manufacturer allowed us to identify that the capsaicin was extracted (that is a single extracted ingredient, which is not herbal) and not an extract from Capsicum fruits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of seven new studies were identified for inclusion in this updated review (Grube 2007; Kosuwon 2010; Randall 2000; Randall 2008; Soltanian 2010; Wang 2012; Widrig 2007). The one study of topical capsaicin that was included in the original review (Deal 1991) was excluded from this review when additional information that was provided by the manufacturer allowed us to identify that the capsaicin was extracted (that is a single extracted ingredient, which is not herbal) and not an extract from Capsicum fruits.…”
Section: Resultsmentioning
confidence: 99%
“…One study compared a herbal product with an active control (Widrig 2007). Another study compared two herbal products against each other as well as against a placebo control in a three-arm trial (Wang 2012). Three studies used crossover designs (Kosuwon 2010; Randall 2000; Soltanian 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Two new herbal patches with ingredients derived from TCM were tested for the first time in a placebo-controlled fashion, and recently reported on in a group of 150 subjects with knee OA [13]. The use of patches is a centuries-old practice in TCM and their preparation involved frying herbs in vegetable oil, discarding the residue, and soaking cloth or paper in the mixture before applying to the injured area or acupoint.…”
Section: Clinical Trials Using Herbal Medicines To Treat Osteoarthritismentioning
confidence: 99%
“…As a folk remedy in China, RAM is primarily used to treat rheumatism, swelling, inflammation, and convulsions. In addition, RAM is commonly used as a key component in formulas for treating RA in Chinese folk medicines such as Lijie Capsule, Fufang Nanxing Zhitong Gao, and Aizheng Zhentong Powder [11][12][13][14]. Previously published investigations indicated that the active components in RA include alkaloids, flavones, guanosines, polysaccharides, γ-aminobutyric acids, dipeptides, and steroids [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%